The Cold Hand Sign in Multiple System Atrophy: Frequency-Associated Factors and Its Impact on Survival - Cao, Bei; Liang, Yan; Zhang, Ling-Yu; Hou, Yan-Bing; Ou, Ru-Wei; Wei, Qian-qian; Shang, Huifang (Frontiers in Aging Neuroscience, 2021)
Background: Few studies focused on the cold hand sign, a red flag symptom, in MSA. Objective: The purpose of the study was to investigate the frequency and correlative factors of cold hand sign (CHS) in multiple system atrophy (MSA) patients, and the impact of its early occurrence on the survival of patients with MSA. Methods: A total of 483 patients with MSA were enrolled in this study, the motor and non-motor symptoms between MSA patients with and without cold hand sign were compared. Moreover, the patients with disease duration ≤ 3 years at baseline, were followed up and analyzed the association between the cold hand sign and survival of MSA. Results: The frequency of cold hand sign in MSA patients was 20%, 15.4%, 25.3% in MSA, MSA-parkinsonian subtype (MSA-P), and MSA-cerebellar type (MSA-C), respectively. Higher Unified Multiple System Atrophy Rating Scale (UMSARS) score and higher Non-Motor Symptom Scale (NMSS) score at the baseline were associated with CHS in MSA. CHS was associated with shorter survival after adjusting for baseline diagnosis subtype, onset age, sex, orthostatic hypotension, disease duration, autonomic onset, UMSARS total score and NMSS score (p= 0.001, HR=3.701, 95% CI=1.765-7.760). Conclusion: CHS was not rare in patients with MSA. The greater disease severity and more severe non-motor symptoms were associated with CHS in MSA. Patients with early occurrence of cold hand sign had a poor prognosis.